Analysis of the Profitability and Marketing Channels of Rice: A Case Study of - M. J, Bime; T. M, Fouda; J. K, Mai Bong (Asian Journal of Agriculture and Rural Development, 2014)
The study carried out in Menchum River valley, Northwest Region of Cameroon had as objective to analyze the profitability and establish the marketing channels of rice in this zone. The study in-terviewed a total of 126 respondents, selected purposively and using the snow ball sampling tech-nique. Results showed that the main actors involved in the rice marketing channel were; produc-ers, wholesalers, hullers, retailers and consumers. The production and marketing of rice in the zone is a profitable venture. In terms of profitability in the rice business, millers obtain a relatively large profit margin as a percentage of the cost price (18.69%) followed by the producers (12.77%), wholesalers (8.5%) then retailers (8.33%). The average profit margin per bag of 50kg was; 1054.5FCFA (franc Communauté financière d’Afrique) for producers, 1963.5 FCFA for millers; 1100 FCFA for the wholesalers and 1250FCFA for the retailers. The principal constraints identi-fied by the study that affects actors of the rice channel were, bad condition of the roads, lack of capital, poor quality of rice. It was recommended that there should be improvement in infrastruc-ture.